Love everlasting. Volume 1 - King, Tom, 1978- (Image Comics, Inc., 2023)
From superstar creators Tom King and Elsa Charretier comes he first volume of a thrilling epic in the tradition of SANDMAN and SAGA. Joan Peterson discovers that she is trapped in an endless, terrifying cycle of "romance"--a problem to be solved, a man to marry--and every time she falls in love she's torn from her world and thrust into another tear-soaked tale. Her bloody journey to freedom and revelation starts in this breathtaking, groundbreaking collected edition.